2013
DOI: 10.1021/ma302275f
|View full text |Cite
|
Sign up to set email alerts
|

An Interface-Driven Stiffening Mechanism in Polymer Nanocomposites

Abstract: Dynamic mechanical response in responsive and adaptive composites can be achieved either through the responsive polymer; with the chemical regulators affecting the bonding between fillers or through reversible covalent bonding. Tuning the interfaces between fillers and polymer matrix potentially plays a critical role in all these systems to enhance their adaptive responses. Here, we present that the bonding–debonding of chains on nanoparticles can be modulated under extensive periodic strains. Mechanical respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 34 publications
1
60
0
Order By: Relevance
“…While uniform dispersion can be ensured with physical adsorption of polymer chains on particles [1][2][3], anisotropic structures can only be obtained when nanoparticles are chemically modified at low densities with polymers [4][5][6]. In the case of particles that are physically adsorbed with chains, strong attractive interactions between a polymer matrix and bare particles lead to uniform and individual particle dispersions at loadings as high as 30 wt% [3,7]. It is also shown that polymer size (R g ) is not affected with the existence of particles in such mixtures [7].…”
Section: Introductionmentioning
confidence: 99%
“…While uniform dispersion can be ensured with physical adsorption of polymer chains on particles [1][2][3], anisotropic structures can only be obtained when nanoparticles are chemically modified at low densities with polymers [4][5][6]. In the case of particles that are physically adsorbed with chains, strong attractive interactions between a polymer matrix and bare particles lead to uniform and individual particle dispersions at loadings as high as 30 wt% [3,7]. It is also shown that polymer size (R g ) is not affected with the existence of particles in such mixtures [7].…”
Section: Introductionmentioning
confidence: 99%
“…Similar contradictory data concerning effect of filler addition on mechanical properties of composites can be found in literature for different polymer‐filler systems (e.g., Refs. , , , , , , ).…”
Section: Resultsmentioning
confidence: 99%
“…Since mechanical properties of samples undergo such cardinal changes at relatively low deformations during DMA, it would be expected that the changes would always take place at the stage of sample preparation for further research. For example, before DSC studies and rheological experiments, composite samples are moulded (and thus subjected to considerable stresses) and also annealed, these being the generally accepted procedures . Heating composite samples before and during calorimetric measurements can be considered as abrupt increase in chain mobility near inhibitory wall (filler surface).…”
Section: Resultsmentioning
confidence: 99%
“…Also in 2013, Wu et al developed polyurethanes grafted with poly (methacrylic acid) chains to allow for the formation of long percolation networks in the inorganic clay composites. Senses and Akcora described a different interesting stiffening mechanism in polymer nanocomposites through a responsive polymer than can control chemical regulators affecting interface physics in the composite or alter crosslinking in the system [94]. The pair used PMMA processed by atom transfer radical polymerization (ATRP) to achieve a polydispersity index of 1.03 and to measure the effects of incorporation of 13-nm silica nanoparticles.…”
Section: Years 2010-2014: Interface Chemistry Of Smpincs Leads To Enhmentioning
confidence: 99%